1995
DOI: 10.1017/s1357729800014107
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of apparent digestibility and voluntary intake of hays fed to sheep: comparison between using fibre components, in vitro digestibility or characteristics of gas production or nylon bag degradation

Abstract: The study compared using chemical components (i.e. crude protein (CP), neutral- and acid-detergent fibre or lignin (NDF, ADF and ADL) g/kg dry matter (DM), the in vitro digestibility (Tilley and Terry, 1963), the in situ (nylon bag) DM degradation (g/100 g DM) and gas production (ml/200 mg DM) techniques to predict voluntary daily intake (g DM per kg M0.75) and in vivo apparent DM digestibility (DMD) of 10 graminaceous hays individually offered ad libitum to four Merino male sheep. Gas production or DM degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 20 publications
5
38
1
7
Order By: Relevance
“…Therefore, the kinetic variables of its IVDMD suggest that spineless cactus could be good forage to ruminants. Linear regression analysis indicated that CP alone in the model gave a high prediction of IVDMD, results which are consistent with those reported by Khazaal et al (1995). The improvement in the prediction of IVDMD was evident when CP, NDF and ADF were included in the model.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the kinetic variables of its IVDMD suggest that spineless cactus could be good forage to ruminants. Linear regression analysis indicated that CP alone in the model gave a high prediction of IVDMD, results which are consistent with those reported by Khazaal et al (1995). The improvement in the prediction of IVDMD was evident when CP, NDF and ADF were included in the model.…”
Section: Discussionsupporting
confidence: 88%
“…ADF di dalam pakan memberikan korelasi negatif terhadap degradasi masing-masing hijauan pakan. Tingginya kadar fraksi serat pada pakan, selain itu lignifikasi pada tahap lebih lanjut juga dapat mengurangi aktivitas degradasi pakan oleh mikrobia rumen, besarnya kandungan lignin tentu saja secara tidak langsung akan memperkecil laju degradasi fraksi potensial terdegradasi (Khazaal et al, 1995). Menurut Van Soest (1994), ADF memberikan pengaruh yang tinggi pada kecernaan hijauan berkisar antara 75-88% dan kandungan ADF pada pasture digunakan sebagai indeks untuk memprediksi tingkat Tabel 6.…”
Section: Degradasi Pakan DI Dalam Rumenunclassified
“…This case is in accordance with the studies and revealed that there were high correlations between in uiuo ME values of roughages and cell wall components such as NDF and especially ADF (Alcicek et al, 1997). In the study, ADL with GP gave a very low R2 value of 0.61 as compared to 0.81 value of Khazaal et al (1995) …”
Section: Resultsmentioning
confidence: 67%